Cardiac function and exercise capacity in patients with metabolic syndrome: A cross-sectional study - Chen, Jiming; Wang, Xing; Dong, Bin; Liu, Chen; Zhao, Jingjing; Dong, Yugang; Liang, Weihao; Huang, Huiling (Frontiers in Cardiovascular Medicine, 2022)
Background Metabolic syndrome is a pre-diabetes condition that is associated with increased cardiovascular morbidity and mortality. We aimed to explore how exercise capacity, cardiac structure, and function were affected in patients with metabolic syndrome. Methods Outpatients with echocardiography and exercise stress test combined with impedance cardiography (ETT + ICGG) results available from Nov 2018 to Oct 2020 were retrospectively enrolled. Echocardiographic, ETT + ICG profiles, and exercise performance were compared between patients with metabolic syndrome and the ones without. Sensitivity analyses were performed excluding patients without established coronary heart disease and further 1:1 paired for age and gender, respectively. Multiple linear regression was used to find out related predictors for maximal metabolic equivalents (METs). Results Three hundred and twenty-third patients were included, among whom 97 were diagnosed as metabolic syndrome. Compared to patients without metabolic syndrome, echocardiography showed that patients with metabolic syndrome had a significantly lower E/A ratio (p < 0.001). Besides, they have larger left atrium, larger right ventricle, and thicker interventricular septum (all p < 0.001), but similar left ventricular ejection fraction (P = 0.443). ICG showed that patients with metabolic syndrome had significantly higher stroke volume at rest and maximum (p < 0.001), higher left cardiac work index at rest and maximum (p = 0.005), higher systemic vascular resistance (SVR) at rest (p < 0.001), but similar SVI (p = 0.888). During exercise, patients with metabolic syndrome had lower maximal METs (p < 0.001), and a higher proportion suffering from ST-segment depression during exercise (p = 0.009). Sensitivity analyses yielded similar results. As for the linear regression model, 6 independent variables (systolic blood pressure, BMI, E/A ratio, the height of O wave, the peak value of LCWi, and the baseline of SVR) had statistically significant effects on the maximal METs tested in exercise (R = 0.525, R2 = 0.246, P < 0.001). Conclusion Patients with metabolic syndrome had significant structural alteration, apparent overburden of left ventricular work index, pre-and afterload, which may be the main cause of impaired exercise tolerance.